2022
DOI: 10.3390/ijtpp7030020
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Turbine Blade Aerodynamic Designs Using CFD and Neural Network Models

Abstract: Optimization methods have been widely applied to the aerodynamic design of gas turbine blades. While applying optimization to high-fidelity computational fluid dynamics (CFD) simulations has proven capable of improving engineering design performance, a challenge has been overcoming the prolonged run-time due to the computationally expensive CFD runs. Reduced-order models and, more recently, machine learning methods have been increasingly used in gas turbine studies to predict performance metrics and operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Traditional design methods rely on experimental data or numerical simulations (Zou et al, 2018), but these have limitations: experimental methods are costly and inflexible, while simulations are computationally complex and subjective (Zou et al, 2018). To overcome these challenges, researchers integrate advanced optimization algorithms with simulation technology (Zhang and Janeway, 2022). Popov et al (2023) redesigned a two-stage turbine using the IOSO software, resulting in a commendable 0.63% improvement in aerodynamic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional design methods rely on experimental data or numerical simulations (Zou et al, 2018), but these have limitations: experimental methods are costly and inflexible, while simulations are computationally complex and subjective (Zou et al, 2018). To overcome these challenges, researchers integrate advanced optimization algorithms with simulation technology (Zhang and Janeway, 2022). Popov et al (2023) redesigned a two-stage turbine using the IOSO software, resulting in a commendable 0.63% improvement in aerodynamic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The surrogate model used for monitoring health is the main novelty of the proposed paper. There have already been many studies that have shown the fact that an ANN consumes less time than FEM analysis [26][27][28]; therefore, it is a suitable approach for jet engine health monitoring rather than FEM.…”
Section: Introductionmentioning
confidence: 99%
“…CFD also can be used to analyze the efficiency between piano key weir and rectangular labyrinth weir to handle increased flood flows [12], gas turbines [28], photo bioreactors [14], metallurgy, biomedicine, and general industrial process [4]. In this study, CFD is being used to analyze fire smoke dispersion patterns and temperature distribution patterns around the fire building Previous study has shown that the shape of the roof could greatly alter the parameters of the flow pattern and pollution distribution, it demonstrated how the height and design of buildings' roofs could drastically alter how street canyons' flow patterns behaved, affecting how pollutants were distributed [9].…”
Section: Introductionmentioning
confidence: 99%